PENGARUH PERSEPSI KEGUNAAN, PENGARUH SOSIAL DAN KEBIASAAN TERHADAP NIAT BERALIH PADA PENGGUNA DOMPET DIGITAL - Kusuma Dewi, Erika Rahma; Artanti, Yessy (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.09.TAHUN.2021, 2021)
As technology evolves, the use of e-wallet is increasing in Indonesia. However, the increasing use of e-wallet indicates uncertain consumer behavior in the choice of e-wallet brands. OVO is the e-wallet with the largest users in Indonesia in 2019. Meanwhile in 2020 the digital wallet with the largest user in Indonesia is ShopeePay. This study aims to analyze the effects of perceived usefulness, social influence, and habit on switching intention OVO users to ShopeePay. This research uses non probability sampling and judgemental sampling with characteristic of respondents were OVO users, are looking for information about ShopeePay with an age range of 20-40 years as many 200 respondents. Data collection was carried out by distributing online questionnaires. Data analysis teqniques using multiple linear regression. The results of this study examined while perceived usefulness, social influence, and habit had significant effects on switching intention